Norcholic Acid Promotes Tumor Progression and Immune Escape by Regulating Farnesoid X Receptor in Hepatocellular Carcinoma - Gong, Yihang; Li, Kun; Qin, Yunfei; Zeng, Kaining; Liu, Jianrong; Huang, Shaozhuo; Chen, Yewu; Yu, Haoyuan; Liu, Wei; Ye, Linsen; Yang, Yang (Frontiers in Oncology, 2021)
Accumulating evidence shows a close association between various types of bile acids (BAs) and hepatocellular carcinoma (HCC), and they have been revealed to affect tumor immune response and progression mainly by regulating Farnesoid X receptor (FXR). Nevertheless, the roles of Norcholic acid(NorCA) in HCC progression remain unknown yet. In this study, herein we demonstrate that NorCA can promote HCC cell proliferation, migration and invasion through negatively regulating FXR. Additionally, NorCA can increase PD-L1 level on the surfaces of HCC cells and their exosomes, and NorCA-induced exosomes dramatically dampen the function of CD4+T cells, thereby inducing an immunosuppressive microenvironment. Meanwhile, a negative correlation between PD-L1 and FXR expression in human HCC specimens was identified, and HCC patients with FXRlowPD-L1high expression exhibit a rather dismal survival outcome. Importantly, FXR agonist (GW4064) can synergize with anti-PD-1 antibody (Ab) to inhibit HCC growth in tumor-bearing models. Taken together, NorCA can promote HCC progression and immune invasion by inhibiting FXR signaling, implying a superiority of the combination of FXR agonist and anti‐PD‐1 Ab to the monotherapy of immune checkpoint inhibitor in combating HCC. However, more well-designed animal experiments and clinical trials are warranted to further confirm our findings in future due to the limitations in our study.